THE ASSOCIATION BETWEEN WOMEN’S EMPOWERMENT AND ANTENATAL CARE COVERAGE IN INDONESIA IN 2017 - Salsabila Putri Lamiday; Putri Bungsu Machmud (Universitas Airlangga, 2019)
Background: Antenatal care coverage (ANC) in Indonesia has been constantly increasing over the years according to the country’s national survey data; however, there is a huge gap in coverage between women with different background characteristics. Purpose: The objective of this study is to determine the association between women’s empowerment and ANC coverage in Indonesia in 2017. Methods: This study used data sourced from the Indonesian Demographic Health Survey (IDHS) 2017 with a cross-sectional study design. The population study was married women aged 15–49 years who had delivered children in the two years before the survey was conducted. About 6,397 samples were obtained by a total sampling method that met inclusion and exclusion criteria. Variables analysed in this study were women’s empowerment and antenatal care coverage. The data analysis used were chi square and multiple logistic regression analysis. This study was conducted in February–April 2019 in all provinces in Indonesia which were the location of the IDHS 2017. Results: The result of multivariate analysis claimed an association that was statistically significant (p value = 0.00) between women’s empowerment and ANC coverage, with adjusted prevalence ratio = 1.05 (95% CI: 1.02–1.08). Conclusion: The conclusion of this study is that less empowered women were 1.05 times more likely to not receive complete and standardised antenatal care compared to women who were more empowered.